Obliczanie Skończonych Sprężysto-Plastycznych Ugięć Prętów Słabo Zakrzywionych - Radwańska, M. (Engineering Transactions, 1972)
The paper deals with the geometrically nonlinear analysis of rods made of elastic-plastic materials with multiple hardening, i.e. of the sectionally linear elastic materials. In Sec. 1 are discussed the difficulties encountered in calculating the geometrically and physically nonlinear rods, and simplifications introduced by various authors are listed; fundamental assumptions are given. Section 2 presents the equations of a deformed rod and their application to the simplified «multipoint» cross-section model according to [D and 8]. Section 3 contains the formal solution of the resulting equation of the deflection curve. Section 4 presents the method of effective numerical integration of the equations (based on earlier papers of one of the co-authors), while Sec. 5 gives the calculation scheme prepared for the «ODRA 1013» electronic computer and a numerical example concerning a statically determinate sandwich arch. Section 6 constitutes a summary of the paper.